Ivermectin environmental impact: Excretion profile in sheep and phytotoxic effect in Sinapis alba - Vokřál, Ivan; Michaela, Šadibolová; Radka, Podlipná; Jiří, Lamka; Lukáš, Prchal; Dominika, Sobotová; Kateřina, Lokvencová; Barbora, Szotáková; Lenka, Skálová (Ecotoxicology and environmental safety, 2019)
Ivermectin (IVM), a macrocylic lactone from the avermectin family, is a potent broad-spectrum anthelmintic drug widely used in veterinary as well as human medicine. Although the health benefits of IVM treatment are particularly important, this drug also represents an environmental pollutant with potentially negative effects on many non-target species. To evaluate the ecotoxicological risk of IVM administration to livestock, information evaluating achievable environment-reaching concentration is needed. Therefore, the present study was designed to determine the excretion profile of subcutaneously administered IVM in sheep. The standard recommended dose of IVM (0.2 mg kg-1 b.w.) was used. UHPLC/MS/MS was used for the analysis of IVM faecal concentration. In addition, the effect of IVM on seed germination and early roots growth of white mustard (Sinapis alba L.) was evaluated in order to estimate the potential phytotoxic effect of IVM. Based on the obtained results, the parameters of IVM pharmacokinetics (maximum concentration (cmax), time to achieve maximum concentration (tmax), mean residence time (MRT), area under the curve (AUC)) were calculated. IVM elimination in sheep was slow, but faster than the elimination reported previously in cattle. Great interindividual differences were also observed. A two-peak profile of concentration curves indicate the importance of the active efflux of IVM via enterocytes. A "seed germination and early roots growth" test revealed significant IVM phytotoxicity (20% inhibition of root growth) even at 50 nM concentration, a level which may be found in the environment. This newly demonstrated phytotoxicity of IVM together with its well-known toxicity to invertebrates should be taken into account, and thus animals treated with IVM should not be kept in pastures, especially not in sites with high ecological value.
Keywords: Feces; Sinapis; ekotoxikologie; Ecotoxicity; Faeces; ovce; plocha pod křivkou; skot; Injections, Subcutaneous; Plants; znečištění životního prostředí; Environmental Pollution; Anthelmintics; Ivermectin; zvířata; feces; Cattle; hořčice rodu Sinapis; Area Under Curve; Sheep; anthelmintika; injekce subkutánní; ivermektin; Ecotoxicology; Animals